Is wine a safe-haven? Evidence from a nonparametric causality-in-quantiles test - Antonakakis, Nikolaos; Balcilar, Mehmet; Bouri, Elie I.; Gupta, Rangan (Asia University michael.mcaleer@gmail.com, 2018)
Unlike the extant literature on safe-havens, where one aims to relate the movements in an asset considered with extreme episodes in equity markets, we test this property for fine wine, by relating it to global uncertainty. Using a nonparametric k-th order causality-in-quantiles test, we show that, while uncertainty does affect returns and/or variance of the alternative wine indices considered, this effect is restricted to only certain parts of the conditional distribution. In particular, wine seems to be unaffected by global uncertainty, and hence, acts as a safe-haven at extreme ends of the market, i.e., during bear or bullish times; but not during normal times (around the median of the conditional distribution of returns and/or volatility). © 2018 Hindawi Limited. All rights reserved.
Keywords: Global uncertainty; Nonparametric quantile causality; Safe-haven; Wine returns and volatility